Portofolio Optimal Investasi Saham dari 6 Sektor pada Indeks LQ45 Periode 2015-2018: Optimal Portfolio Stock Investment from 8 Sectors of LQ45 During Period 2015-2018 - Verkino, Benyamin; Sinaga, Bonar M.; Andati, Trias (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
The purpose of this research is to build an optimum investment portfolio of stocks using Single Index Model (SIM) from 31 stocks of 8 sectors LQ45 indices (trade, mining, infrastructure, consumer, industry, agriculture, finance, and properti) during period 2015-2018. Based on the result of research, investor can form an investment portfolio that consists of 4 stocks (BBCA, SRIL, PTBA, and WSKT from finance, industry, mining, and property sectors) with portfolio’s expected rate of return of 0.351% per week and portfolio’s variance of 0.039% per week, compared with IHSG’s rate of return and variance for 0.091% and 0.037% per week. Signifcance’s test using one sample t-test shows portfolio’s return is significantly greater compared with market’s return or IHSG. Performance measurement of portfolio by using Sharpe, Treynor, and Jensen’s ratio shows a positive ratio compared to IHSG (Sharpe 0.117, Treynor 0.002, Jensen: 0,002) which means this portfolio will give higher rate of return than what is being offered by IHSG.Keywords: IHSG, LQ45, portfolio, sector, single index model